Executive Cognitive Functions and Behavioral Control Differentially Predict HbA1c in Type 1 Diabetes across Emerging Adulthood. (11th April 2020) - Suchy, Yana; Butner, Jonathan; Wiebe, Deborah J.; Campbell, MaryJane; Turner, Sara L.; Berg, Cynthia A.
Abstract: Objectives: To examine the contributions of two aspects of executive functioning (executive cognitive functions and behavioral control) to changes in diabetes management across emerging adulthood. Methods: Two hundred and forty-seven high school seniors with type 1 diabetes were assessed at baseline and followed up for 3 years. The baseline assessment battery included performance-based measures of executive cognitive functions, behavioral control, IQ estimate (IQ-est), and psychomotor speed; self-report of adherence to diabetes regimen; and glycated hemoglobin (HbA1c) assay kits as a reflection of glycemic control. Results: Linear and quadratic growth curve models were used to simultaneously examine baseline performance on four cognitive variables (executive cognitive functions, behavioral control, IQ, and psychomotor speed) as predictors of indices of diabetes management (HbA1c and adherence) across four time points. Additionally, general linear regressions examined relative contributions of each cognitive variable at individual time points. The results showed that higher behavioral control at baseline was related to lower (better) HbA1c levels across all four time points. In contrast, executive cognitive functions at baseline were related to HbA1c trajectories, accounting for increasingly more HbA1c variance over time with increasing transition to independence. IQ-est was not related to HbA1c levels or changes over time, but accounted instead for HbA1c variance at baseline (while teens were still living at home), above and beyond all other variables. Cognition was unrelated to adherence. Conclusions: Different aspects of cognition play a different role in diabetes management at different time points during emerging adulthood years.